If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 3c = 12 Solving 2b + 3c = 12 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3c' to each side of the equation. 2b + 3c + -3c = 12 + -3c Combine like terms: 3c + -3c = 0 2b + 0 = 12 + -3c 2b = 12 + -3c Divide each side by '2'. b = 6 + -1.5c Simplifying b = 6 + -1.5c
| -9+4x=6x+-13 | | 8-10y=-8y | | b-5+8b=33 | | 226.8=21.7y | | 8m(m-3)=56 | | -80-11x=5x+144 | | 216x+36=15+12x | | 3(r-3)+7r=54 | | y=8-6 | | y+g=12 | | 20y+3y= | | 216=36x+15+12x | | 24=w+8 | | 5x-11+5x=21 | | 5+4w=-8 | | 216+36x=15+12x | | 16y+11y= | | 5n^2+19n-69=-2 | | 24=w+6 | | 3y+1=21 | | -8x-163=101+3x | | -7.2=80x | | 17x=26 | | 8x-13x=26-34 | | 3m-[m+1]=6m+1 | | 42.34=9g+3.82 | | 6x-9=110-11x | | 7x+1=2x-4 | | 5x+2(3x+8)+17=4x+21 | | 5-3(x-7)=2(2-x) | | 2m^3(4m^2)= | | 4(x^3-6x^2+9)=0 |